Subsidy Reform in the Middle East and North Africa : Recent Progress and Challenges Ahead - Sdralevich, Carlo (Departmental Papers; Departmental Paper ;, 2014)
In the Middle East and North Africa (MENA) countries price subsidies are common, especially on food and fuels. However, these are neither well targeted nor cost effective as a social protection tool, often benefiting mainly the better off instead of the poor and vulnerable. This paper explores the challenges of replacing generalized price subsidies with more equitable social safety net instruments, including the short-term inflationary effects, and describes the features of successful subsidy reforms.